Keadilan Bagi Pihak Korban Dalam Release And Discharge Agreement Transportasi Udara Yang Dilegalisasi Oleh Notaris Dalam Kasus Kecelakaan Pesawat Lion Air Jt610 - Lucyanna Nilasary; Chandra Yusuf; Mohammad Ryan Bakry (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In creating legal certainty, justice and protection for the community, the rule of law is needed that can accommodate all aspects of life because the purpose of law is to create a sense of justice in society.In the case of the Lion Air JT610 plane crash, the process of paying compensation to the families of the victims still experienced obstacles, namely the existence of a Release and Discharge Agreement which was then legalized by a Notary, as an absolute requirement for disbursement of compensation. The victims' families are asked to waive their rights in their entirety so that they do not make demands to any party deemed responsible for the accident.The formulation of the problem in this study aims to analyze the legal aspects of the Release and Discharge Agreement legalized by Notary and find a form of justice based on the principles of justice for the victims' families by looking at the forms of responsibility of the parties involved in the Lion Air JT610 plane crash.The method used is normative juridical through a statutory approach, concept approach and case approach. It is concluded that the Release and Discharge Agreement can be declared null and void because its contents violate the laws and regulations in Indonesia and violate human rights, the victims can still claim their rights to the parties related to the plane crash without eliminating their rights from others.In this case Lion Air still has to fulfill its obligation to pay compensation without any conditions so that the victims get justice.